THE EFFECTIVITY OF MATHEMATICS LEARNING THROUGH POLYA’S HEURISTIC STRATEGY WITH SCIENTIFIC APPROACH IN TERM OF MATHEMATICAL CREATIVE THINKING ABILITY AND THE AUTONOMOUS LEARNING OF SMK PGRI 1 SENTOLO STUDENTS - Agusti Eka Dyah Larasati; Djamilah Bondan Wijajanti (Universitas Negeri Yogyakarta, 2016)
The aim of this research was to identify the effectiveness of the mathematics teaching and learning through Polya’s heuristic strategy with scientific approach in term of the mathematical creative thinking ability and the autonomous learning of SMK PGRI 1 Sentolo students. The design of this research was one group pretest posttest design. The population of this research was class of X in SMK PGRI 1 Sentolo which was three classes and the research sample was the students of Class X AK 1. The factor of this research was the Mathematics teaching and learning by using the Polya’s heuristic strategy combined with scientific approach, while the response was the mathematical creative thinking ability and the autonomous learning of the students. Hypothesis testing for the mathematical creative thinking ability data would use the effective criteria if the mean score of post-test was more than the mean score of the pre-test and the students score percentage which achieved more than or equal to 75 was more than 75%. Hypothesis testing for the autonomous learning data would use the effective criteria if the mean score of the final questionnaire was more than the mean score of the first questionnaire and the students score percentage which achieved the good category was more than 75%. Based on the hypothesis testing which used a significance level of 5%, it could be concluded that the Mathematics teaching and learning by using the Polya’s heuristic strategy combined with scientific approach was effectively implemented in SMK PGRI 1 Sentolo observed from the mathematical creative thinking ability and the autonomous learning of the students. Keywords: scientific, Polya’s heuristic, creative thinking, autonomous learning.